Changes in the Language of the Reformed Church in the Second Half of the 20ᵗʰ Century: The Convergence of Oral History and Big Data - Gergely HANULA (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The author’s journey begins with a deep immersion in his traditional Protestant faith, where he was taught to thoroughly know both the Old and the New Testament. As he reflects on his faith, the concept of being a “stranger and sojourner” comes to the forefront, highlighting the feeling of alienation within the secular world.